AL-QUR’AN TENTANG LUPA, TIDUR, MIMPI DAN KEMATIAN - Wahyudi Setiawan (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2016)
Qur'an become the main source of the Muslims as a guide to life in the world's happiness hereafter. Various themes in the Qur'an constantly by each generation intensely studied and developed in a variety of disciplines, some parts of the theme is about forgetting, sleep, dream, and death. Forget, sleep, dream, and death is the other side of human existence as a perfect being. However, so there are some among the other parts of man she did not know, even beyond the ability of themselves as being perfect. Emotional, mental, and psychology is part of the complexity of the human element that makes it as the perfect beings. From various disciplines, especially psychology intense discusses forget, sleep, dream, and death, the Qur'an has submitted a concept of humanity intact, ranging from inner and outer regions, from physical to psychological matter, from the visible or unseen. Forget, sleep, dream, and death is the other side of the man she had lived. Real existence and every human being must undergo in accordance with instinct and human nature as well as servants of God.Keywords: Psychology, Lost, Sleep, Dream, and Death